2016
DOI: 10.1292/jvms.15-0450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PCV2 antigen in the ovarian tissues of gilts

Abstract: The present study was performed to determine the expression of porcine circovirus type 2 (PCV2) antigen in the ovarian tissue of naturally infected gilts. Ovarian tissues were obtained from 11 culled gilts. The ovarian tissues sections were divided into two groups according to PCV2 DNA detection using PCR. PCV2 antigen was assessed in the paraffin embedded ovarian tissue sections by immunohistochemistry. A total of 2,131 ovarian follicles (i.e., 1,437 primordial, 133 primary, 353 secondary and 208 antral folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Since the emergence of PCV2 and PCV3, continuous studies have explored the pathogenesis and prevalence of these two viral diseases (Kwon et al., 2017 ; Opriessnig et al., 2007 ; Park & Chae, 2021 ; Tischer et al., 1974 ; Tummaruk & Pearodwong, 2016 ). In this study, we investigated the prevalence of PCV2 and PCV3 in slaughtered pigs and wild boars between 2018 and 2019 in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the emergence of PCV2 and PCV3, continuous studies have explored the pathogenesis and prevalence of these two viral diseases (Kwon et al., 2017 ; Opriessnig et al., 2007 ; Park & Chae, 2021 ; Tischer et al., 1974 ; Tummaruk & Pearodwong, 2016 ). In this study, we investigated the prevalence of PCV2 and PCV3 in slaughtered pigs and wild boars between 2018 and 2019 in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study reported that sick pigs and healthy pigs showed similar PCV3‐positive rates in their serum (Saporiti et al., 2020 ). However, the role of PCV2 and PCV3 in pigs disease is still controversial (Kixmöller et al., 2008 ; Ku et al., 2017 ; Mora‐Díaz et al., 2020 ; Opriessnig et al., 2007 ; Temeeyasen et al., 2021 ; Tummaruk & Pearodwong, 2016 ). Therefore, continuous prevalence investigation and further pathogenesis study, as well as other factors of disease progress, are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings collectively show that PCV2-con-taminated semen can be singular potential harms to spermatozoa prior to fertilization. Tummaruk et al (2016) assessed the expression of PCV2 antigen in ovarian tissues of gilts. Their findings indicated that PCV2 antigen was expressed in all types of ovarian follicles and corpora lutea in naturally PCV2-infected gilts.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, Zika virus replicated in ovary and infected the granulosa cells as well as the theca cells in antral follicles, which significantly damaged ovarian structure and further disrupted the estrous cycle and prolonged pregnancy by causing disordered ovarian steroidogenesis [ 17 ]. Moreover, the expression of porcine circovirus type 2 antigen was detectable in ovarian tissues of naturally infected gilts [ 18 ]. However, it is still unknown whether PRV could infect the ovarian granulosa cells and disrupt cell function, leading to abnormal ovarian function in sows.…”
Section: Introductionmentioning
confidence: 99%